THEORETICAL ANALYSIS OF FEATURES OF THE ASSESSMENT OF INVESTMENT PROJECTS - A. Zinchenko; A. Sazonov; M. Yudin (Вестник университета)
Problems of an assessment of economic efficiency of investment projects are investigated. By results of the analysis of the main criteria of an assessment of economic efficiency of investments shortcomings of the main criteria and their contradictory character are revealed.